2015
DOI: 10.1016/j.ygeno.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of copy number variations by SNP50 BeadChip array in Chinese sheep

Abstract: The sheep (Ovis aries) plays a major socio-economic role in the world. Copy number variations (CNVs) are increasingly recognized as a key and potent source of genetic variation and phenotypic diversity, but little is known about the extent to which CNVs contribute to genetic variation in Chinese sheep breeds. Analyses of CNVs in the genomes of eight sheep breeds were performed using the sheep SNP50 BeadChip genotyping array. A total of 111 CNV regions (CNVRs) were obtained from 160 Chinese sheep breeds. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 46 publications
5
42
1
1
Order By: Relevance
“…Liu 16 identified 238 CNVRs by assessing 329 individuals from 3 breeds using the Ovine SNP 50 BeadChip, but only 12 of these CNVRs on 10 chromosomes were also identified in our results ( Supplementary File 1: Table S8 ). The most recent study on CNV in sheep was carried out by Ma 17 , who identified 111 CNVRs by subjecting 160 individuals from 8 breeds to analysis using the Ovine SNP 50 BeadChip; only 8 of these CNVRs on 4 chromosomes were also identified in our results ( Supplementary File 1: Table S9 ).…”
Section: Resultsmentioning
confidence: 73%
“…Liu 16 identified 238 CNVRs by assessing 329 individuals from 3 breeds using the Ovine SNP 50 BeadChip, but only 12 of these CNVRs on 10 chromosomes were also identified in our results ( Supplementary File 1: Table S8 ). The most recent study on CNV in sheep was carried out by Ma 17 , who identified 111 CNVRs by subjecting 160 individuals from 8 breeds to analysis using the Ovine SNP 50 BeadChip; only 8 of these CNVRs on 4 chromosomes were also identified in our results ( Supplementary File 1: Table S9 ).…”
Section: Resultsmentioning
confidence: 73%
“…This difference is not surprising, as the current study used a high-density SNP array containing more than 600 K probes, whereas Ma et al . 11 and Liu et al . 10 used low-density SNP arrays with 50 K probes.…”
Section: Discussionmentioning
confidence: 94%
“…The CNVRs identified in these previous studies were different to some extent, which may have been related to the differences in sheep breeds, sample sizes, CNV detection platforms and CNV calling algorithms used. However, it is noteworthy that the CNVRs identified in this study had high overlapping ratios ( [7,11,13,15,16,28]. The four studies with which there were high overlapping ratios all used Chinese indigenous sheep breeds or Chinese cultivated sheep breeds as the study subjects, whereas the two studies with which there were low overlapping ratios used foreign sheep breeds.…”
Section: Discussionmentioning
confidence: 71%